Complications and Long-Term Outcomes of Shunted Post-Traumatic Hydrocephalus: A Single-Center Series - Eric A. Grin; Alexander Eremiev; Adhith Palla; Daniel de Souza; Michael Farid; David H. Harter (Neurotrauma Reports)
Post-traumatic hydrocephalus (PTH) is a particularly challenging complication of traumatic brain injury (TBI). The primary treatment for PTH is placement of a ventricular shunt. However, shunts are associated with high complication rates regardless of placement indication. PTH is understudied compared with other TBI sequelae, and long-term outcomes remain poorly characterized. We report our institution’s experience with shunted PTH over the last decade. Fifteen patients presented with TBI between January 2014 and April 2024 and underwent at least one shunt placement for diagnosed PTH. Patients’ demographics, injury characteristics, clinical courses, and outcomes were manually extracted from electronic medical records. Most patients were male (86.7%), White (33.3%), and suffered a severe TBI (Glasgow Coma Scale score 3–8). Four (26.7%) patients underwent shunt placement within 1 month of TBI, 9 (60.0%) within 3 months, 13 (86.7%) within 1 year, and all patients within 2 years. At least one shunt failure occurred in 53.3% of patients, and multiple failures requiring revision surgery occurred in 46.7%; all but one patient had their initial shunt failure occur within 1 year of placement. The most common reasons for shunt failure were catheter obstruction (26.3%) and infection (26.3%). Patients had a median follow-up of 2.8 years and an overall mortality rate of 13.3%. Of the surviving patients, a favorable long-term outcome (Glasgow Outcome Scale 4–5) was achieved in 26.7%. Notably, 6/15 (40.0%) patients experienced early post-traumatic seizures (ePTS). Only 4/10 patients who developed post-traumatic epilepsy (PTE) had experienced ePTS, challenging existing literature’s suggestion that ePTS most reliably predicts PTE development. Combining our cohort with that of an underrecognized report from 2000, we report a cumulative 61.9% incidence of PTE in shunt-dependent PTH, which, to our knowledge, is the highest reported incidence of PTE in current literature. The presence of shunted PTH following TBI may thus increase the risk profile for developing PTE.